Institutional resilience and crisis governance in the EU: insights from the Lisbon Metropolitan Experience - Gonçalves, Jorge; Spolaor, Silvia; Lebedeva, Larysa (Frontiers in Political Science, 2025)
This article explores the role of metropolitan institutions in crisis governance, drawing on the case of the Lisbon Metropolitan Area (LMA) during the COVID-19 pandemic. While formal decision-making in Portugal remained centralized, local institutions were critical in implementing emergency responses, sustaining services, and supporting vulnerable populations. Based on survey data from 90 public and associative entities, the analysis reveals high levels of institutional adaptability and lateral cooperation, despite the absence of coordinated metropolitan governance. However, responses were primarily adaptive rather than transformational, and structural challenges, including digital inequality, fragmented coordination, and lack of institutional learning, persisted. The findings highlight the need to integrate metropolitan actors more fully into EU crisis governance frameworks, not merely as implementers but as co-designers of inclusive and resilient responses. The Lisbon experience underscores both the potential and limitations of emergent, bottom-up resilience and calls for the institutionalization of metropolitan governance as a key dimension of future EU crisis preparedness.